Mastery of Pedagogical Content Knowledge for Students of Natural Science Education - Sri Murni Soenarno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
The Law of The Republic of Indonesia number 14 in 2005 concerning Teacher and Lecturer opened opportunities for a fresh graduate of S1/D4 programs to become a teacher. This opportunity is a big challenge for a fresh graduate of Natural Sciences Education Program in competition against a fresh graduate of pure natural sciences program to be a teacher. This study was a literature study and observation. The purpose of this study was to explain how to prepare undergraduate students of Natural Sciences Education Program facing competition to become teachers. The result of this study showed that the mastery of pedagogical content knowledge becomes important for the students of Natural Sciences Education Program to show their advantages in employment competition.